Advanced breast cancer in a relatively young man with severe obesity and type 2 diabetes mellitus. Issue 3 (May 2017) - Obata, Atsushi; Okauchi, Seizo; Kimura, Tomohiko; Hirukawa, Hidenori; Tanabe, Akihito; Kinoshita, Tomoe; Kohara, Kenji; Tatsumi, Fuminori; Shimoda, Masashi; Kamei, Shinji; Nakanishi, Shuhei; Mune, Tomoatsu; et al.
Abstract : It is known that male breast cancer is extremely rare and obesity is a strong risk factor of breast cancer in both male and female. In general, the prognosis in breast cancer in males is known to be very poor compared to that in females as it tends to be more advanced stage due to delayed initial diagnosis. Therefore, we should be aware of the possibility that breast cancer could be developed even in relatively young males without any specific risk factors especially when the subjects have severe obesity.